German television : historical and theoretical approaches - Powell, Larson, 1960-; Shandley, Robert R. (Film Europa, 2016)
Long overlooked by scholars and critics, the history and aesthetics of German television have only recently begun to attract serious, sustained attention, and then largely within Germany. This ambitious volume, the first in English on the subject, provides a much-needed corrective in the form of penetrating essays on the distinctive theories, practices, and social-historical contexts that defined television in Germany. Encompassing developments from the dawn of the medium through the Cold War and post-reunification, this is an essential introduction to a rich and varied media tradition.